Aberrant expression of MICO1 and MICO1OS in deceased somatic cell nuclear transfer calves. Issue 6 (24th April 2017) - Wang, Guan‐Nan; Yang, Wen‐Zhi; Xu, Da; Li, Dong‐Jie; Zhang, Cui; Chen, Wei‐Na; Li, Shi‐Jie
Abstract : Incomplete reprogramming of a donor nucleus following somatic cell nuclear transfer (SCNT) results in aberrant expression of developmentally important genes, and is the primary source of the phenotypic abnormalities observed in cloned animals. Expression of non‐coding RNAs in the murine Dlk1‐Dio3 imprinted domain was previously shown to correlate with the pluripotency of mouse induced pluripotent stem cells. In this study, we examined the transcription of the bovine orthologs from this locus, MICO1 (Maternal intergenic circadian oscillating 1) and MICO1OS ( MICO1 opposite strand), in tissues from artificially inseminated and SCNT calves that died during the perinatal period. A single‐nucleotide polymorphism (SNP), a T‐to‐C transition, was used to analyze the allelic transcription of MICO1 . Our results indicate monoallelic expression of the MICO1 C allele among the six analyzed tissues (heart, liver, spleen, lung, kidney, and brain) of artificially inseminated calves, indicating that this gene locus may be imprinted in bovine. Conversely, we observed variable allelic transcription of MICO1 in SCNT calves. We asked if DNA methylation regulated the monoallelic expression of MICO1 and MICO1OS by evaluating the methylation levels of six regions within or around this locus in tissues with normal or aberrant MICO1 transcription; all of the samples from either artificially inseminated or SCNT calves exhibited hypermethylation, implying that DNA methylation may not be involved in regulating its monoallelic expression. Furthermore, three imprinted genes ( GTL2, MEG9, and DIO3 ) nearby MICO1 showed monoallelic expression in SCNT calves with aberrant MICO1 transcription, indicating that not all of the genes in the bovine DLK1‐DIO3 domain are mis‐regulated.